Critical thinking skills : effective analysis, argument and reflection - Cottrell, Stella (London : Bloomsbury, 2023)
How well do they say it? -- 6 Reading between the lines -- Introduction -- Assumptions -- Activity: Identify the underlying assumptions -- Identifying hidden assumptions -- Implicit assumptions used as reasons -- Activity: Implicit assumptions used as reasons -- Inference, assumption and syllogism -- False premises -- Activity: False premises -- Implicit arguments -- Activities: Implicit arguments -- Denoted and connoted meanings -- Activities: Associations and stereotypes -- Activity: Denoted and connoted meanings -- Summary: Reading between the lines -- 7 Does it add up?
Recognising other non-arguments -- Summary: Is it an argument? -- 5 How well do they say it? -- Introduction -- How clear is the author's position? -- Internal consistency -- Activity: Internal consistency -- Logical consistency -- Activity: Logical consistency -- Independent reasons and joint reasons -- Activity: Independent reasons and joint reasons -- Intermediate conclusions -- Intermediate conclusions used as reasons -- Activity: Intermediate conclusions -- Summative and logical conclusions -- Activity: Summative and logical conclusions -- Logical order -- Activity: Logical order
Description based upon print version of record.
Introduction
Includes bibliographical references and index.
OCLC control number change
Keywords: Critical thinking; Study skills; Critical thinking; Study skills; Electronic books